The Role of Health Administration, Social Services, Health Informatics, and Public Health in Driving Digital Transformation in Healthcare Systems: An Integrative Review - Hawsawi, Hadeel Mohammed Ali; Al-Rashidi, Saad Abdullah; Alghamdi, Waleed Ahmed Eidhah; Alghamdi, Mohammed Abdallah Mohammed; Althagafi, Meshal Eid; Alsalmy, Bandar Oraimt; Alharthi, Mohamed Abdulrahman; Alharthi, Abdulaziz Abdulrahman; Alshawqab, Abdullah Saad; Alshehri, Mohammed Meshal; Dosar, Ahmad Mohammed Al; Alhuzali, Hakem Salem (Journal of Posthumanism, 2024)
Introduction: Machine learning, Artificial intelligence and mobile medical software and apps that help physicians' everyday clinical choices are just a few examples of how digital technologies have been revolutionizing healthcare. Tools for digital health have great possibilities for enhancing the performance of personal healthcare in addition to our ability to identify and treat illnesses. Aim of work: for exploring the vital role that public health, social services, health administration, and health informatics play in promoting digital transformation in healthcare systems. Methods: We used the following search phrases to perform an extensive search in the MEDLINE database: role, digital transformation, public health, enhancing, health informatics, and health administration. We conducted a Google Scholar search to discover and look over scholarly reviews related to my review. Certain criteria for inclusion had an impact on the choosing of articles. Results: With distinct headers in the discussion part, the study was divided into several sections. Conclusion: The complete integration of data analytics, digital technologies and creative procedures to improve the quality of healthcare services is known as "digital transformation" in the healthcare section. For the treatment of non-communicable diseases, digital services can be both economical and effective; yet, their generalizability is constrained by the variable treatment effects. To collect, analyze, and apply data to improve health outcomes, health informatics integrates data science, data analytics and information management. To increase the effectiveness of healthcare organizations, technologists create and evaluate data collecting and usage platforms. The usage of advanced analytics technologies and the ongoing geometric development in the quantity of data that can be analyzed will affect almost every side of healthcare, including the management procedures automation, the quality of insurance rates, and the usage of AI in diagnosis. Some important aspects of digital healthcare transformation include Electronic health records, Data analytics, Artificial intelligence, Telemedicine and Wearable devices. Patients can utilize patient portals to access personal health information such as appointment data, medication information and test results. The digital services effects are on the health of population, expenses, and healthcare professional and patient satisfaction, as well as to pinpoint factors that promote and hinder the use of digital services in social welfare and healthcare. Growing in popularity, health information technology enables healthcare medical facilities to use pertinent data to scale forecast and operations treatment outcomes through information systems communication. Automation in the medical field can considerably boost efficiency in numerous healthcare administration jobs like: Streamlining appointment scheduling, maintaining compliance with healthcare regulations and laws, Managing work schedules for caregivers and other staff members and Keeping patient health information.